CXCL1, CCL2, and CCL5 modulation by microbial and biomechanical signals in periodontal cells and tissues—in vitro and in vivo studies - Rath-Deschner, Birgit; Memmert, Svenja; Damanaki, Anna; Nokhbehsaim, Marjan; Eick, Sigrun; Cirelli, Joni A. [UNESP]; Götz, Werner; Deschner, James; Jäger, Andreas; Nogueira, Andressa V. B. (Springer Nature, 2020)
Objectives: This study was established to investigate whether the chemokines CXCL1, CCL2, and CCL5 are produced in periodontal cells and tissues and, if so, whether their levels are regulated by microbial and/or mechanical signals. Materials and methods: The chemokine expression and protein levels in gingival biopsies from patients with and without periodontitis were analyzed by RT-PCR and immunohistochemistry. The chemokines were also analyzed in gingival biopsies from rats subjected to experimental periodontitis and/or orthodontic tooth movement. Additionally, chemokine levels were determined in periodontal fibroblasts exposed to the periodontopathogen Fusobacterium nucleatum and mechanical forces by RT-PCR and ELISA. Results: Higher CXCL1, CCL2, and CCL5 levels were found in human and rat gingiva from sites of periodontitis as compared with periodontally healthy sites. In the rat experimental periodontitis model, the bacteria-induced upregulation of these chemokines was significantly counteracted by orthodontic forces. In vitro, F. nucleatum caused a significant upregulation of all chemokines at 1 day. When the cells were subjected simultaneously to F. nucleatum and mechanical forces, the upregulation of chemokines was significantly inhibited. The transcriptional findings were paralleled at protein level. Conclusions: This study provides original evidence in vitro and in vivo that the chemokines CXCL1, CCL2, and CCL5 are regulated by both microbial and mechanical signals in periodontal cells and tissues. Furthermore, our study revealed that biomechanical forces can counteract the stimulatory actions of F. nucleatum on these chemokines. Clinical relevance: Mechanical loading might aggravate periodontal infection by compromising the recruitment of immunoinflammatory cells.
Keywords: Fusobacterium nucleatum; Gingivitis; Orthodontic tooth movement; Periodontitis; Periodontium